An immunological Method for Detection of the Carrier of Hemophilia B - Matsuoka, Matsuzo; Ito, Masakazu; Takahashi, Kaoru; Sakuragawa, Nobuo (Thrombosis and Haemostasis, 1976)
This paper presents the results of an immunological study of hemophilia B and its carriers which used two kinds of antibodies, a heterologous antibody of high specificity and a homologous antibody developed in a patient with severe hemophilia B.1. The factor IX related antigen for hemophilia B could be determined by a neutralization test and not by a precipitation reaction.2. The activity of factor IX in a definite carrier of hemophilia B was significantly lower than that of factor VIII in a definite carrier of hemophilia A.3. In hemophilia B, there were no differences between the factor IX antigen determined by either the heterologous rabbit antibodies or the homologous antibodies. And there was no discrepancy between the factor IX antigen and the factor IX activity. Therefore, we cannot use this discrepancy for the detection of a carrier of hemophilia B.4. However, there was a discrepancy between the factor IX antigen determined by the neutralization test and the factor IX procoagulant activity in the patients of both hemophilia BM and hemophilia B+. The identical results were obtained in the cases of carriers of both hemophilia BM and hemophilia B+. These facts are very useful for the detection of carriers of hemophilia BM and hemophilia B+.